2004
DOI: 10.1111/j.1600-6143.2004.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA Mismatching Increases the Risk of BK Virus Nephropathy in Renal Transplant Recipients

Abstract: BK virus (BKV)nephropathy is a serious complication in kidney transplant recipients that may lead to irreversible graft failure. We have analyzed the degree of donor/recipient HLA compatibility and HLA antigen association in 40 kidney transplant patients with BKV nephropathy in comparison with a control group of 404 unaffected transplant recipients who were on tacrolimus-based immunosuppression with no induction. HLA compatibility was assessed by determining the number of HLA-A, -B, -DR-mismatched antigens. BK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
8
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 34 publications
7
107
8
3
Order By: Relevance
“…Some authors reported that the injury of the renal allograft may have an important role in the pathogenesis of BKVAN (Drachenberg et al, 2005). The association found between human lymphocyte antigen mismatching and BKVAN supports the hypothesis (Awadalla et al, 2004).…”
Section: Bk Virussupporting
confidence: 73%
“…Some authors reported that the injury of the renal allograft may have an important role in the pathogenesis of BKVAN (Drachenberg et al, 2005). The association found between human lymphocyte antigen mismatching and BKVAN supports the hypothesis (Awadalla et al, 2004).…”
Section: Bk Virussupporting
confidence: 73%
“…Polyclonal induction therapy was recently associated with an increased risk for infectious complications in pediatric renal transplant patients (17). Other studies have reported that use of antilymphocyte agents for the treatment of steroid-resistant rejection is associated with BKV replication in patients who are on tacrolimus or MMF maintenance therapy (7,18,19). However, other studies that examined BKV specifically did not find an association between use of antilymphocyte preparations and risk for BK viruria, viremia, or BKVN (7,16,18,20).…”
Section: Discussionmentioning
confidence: 90%
“…However, other studies that examined BKV specifically did not find an association between use of antilymphocyte preparations and risk for BK viruria, viremia, or BKVN (7,16,18,20). HLA mismatching has been identified as a risk factor for BKVN in both retrospective and prospective studies among adult renal transplant patients (7,19). The increased rejection risk with HLA mismatching (21,22) through its treatment with escalation of immunosuppression and/or via direct rejectionrelated inflammatory responses has been proposed as a potential mechanism for this association.…”
Section: Discussionmentioning
confidence: 99%
“…Awadalla et al (29) showed that the occurrence of BKVN correlates with a higher degree of HLA mismatches, which postulates the role of alloimmune activation. Investigators from Emory University (30) showed using a mouse polyoma transplant model that polyoma viral nephritis occurs only in the presence of alloimmune activation.…”
Section: Pathogenesis Of Bkv Infectionmentioning
confidence: 99%